Dental corrosion in preindustrial societies: A case study of a child from "Pedra do Cachorro" dating to 1,470 BP, Northeastern Brazil - Rodrigo Elias Oliveira; Ana Solari; Sergio Francisco S.M. Silva; Gabriela Martin; Caio Belem Soares; Andre Strauss (Dental Anthropology Association, 2020)
Systemic vomiting resulting from mental disorders and the high intake of acidic beverage in industrial societies result in a relatively elevated frequency of dental corrosion. In the past, however, this type of chemical dental wear was rather rare. Here we describe the case of a 3-year-old child dated to 1470±30BP from the archaeological site of Pedra do Cachorro (northeastern Brazil) that presents a unique pattern of chemical wearing compatible with dental corrosion. We integrate this observation with a broader characterization of buccal health including caries, periapical lesions, dental calculus and periodontal bone resorption. Osteological markers of physiological imperilments such as linear enamel hypoplasia (LEH) and transverse radiopaque lines (Harris lines) are also considered.